A rust cleaning wipe and a method of manufacturing the same
Patent Information
- Application Number
- CN202611227758.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本发明的目的是提供一种除锈清洁擦及制备方法,以解决现有技术中除锈清洁擦多为打磨层、粘接层与擦拭层的简单叠合结构,各层功能单一的问题
[0028]与现有技术相比,本发明提供的一种除锈清洁擦及制备方法,除锈打磨层原位掺杂第一缓蚀组分,打磨除锈的同时对金属新鲜表面即时缓蚀;功能粘接层复配缓蚀因子,作为缓蚀储库持续缓释补充;亲水擦拭层负载钝化清洁组分,擦拭清污时同步在金属表面形成钝化防护膜;三层功能协同,单次作业即可完成锈层去除、过程缓蚀与表面钝化,显著提升除锈后的长效防返锈性能。
Smart Images

Figure CN122875504A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to cleaning abrasive technology, specifically to a rust-removing cleaning abrasive and its preparation method. Background Technology
[0002] Rust removal and cleaning of metal surfaces is widely used in many scenarios such as industrial parts maintenance, hardware product maintenance, and household kitchenware cleaning. Rust removal and cleaning wipes have become the mainstream manual rust removal and cleaning consumables due to their advantages of convenient operation, wide applicability to substrates, and no need for special tools.
[0003] However, existing rust removal and cleaning wipes are mostly simple composite structures of a grinding layer, an adhesive layer, and a wiping layer. Each layer has an independent and single function. The grinding layer only removes rust through the physical friction of the abrasive, the adhesive layer only serves to bond and fix the layers together, and the wiping layer only has basic water absorption and cleaning capabilities. The layers do not form a functionally synergistic protective system, making it impossible to achieve the integrated effect of rust removal, corrosion inhibition, and surface passivation film formation in a single rust removal operation. The exposed fresh metal surface after rust removal is prone to secondary rusting, making it difficult to simultaneously meet the needs of efficient rust removal and long-term rust prevention. Summary of the Invention
[0004] The purpose of this invention is to provide a rust removal cleaning wipe and its preparation method, so as to solve the problem that the existing rust removal cleaning wipes are mostly simple superimposed structures of a grinding layer, an adhesive layer and a wiping layer, and each layer has a single function.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a rust removal and cleaning wipe, comprising a hydrophilic wiping layer, a functional adhesive layer, and a rust removal and polishing layer sequentially arranged from top to bottom;
[0006] The rust removal and polishing layer is configured as a porous foam matrix, which is made of rubber through cross-linking foaming. The porous foam matrix is in situ doped with composite abrasive particles and a first corrosion inhibitor, and the composite abrasive particles are partially exposed on the inner wall and outer surface of the pores of the porous foam matrix.
[0007] The functional adhesive layer is a modified water-based adhesive layer with compound corrosion inhibitors;
[0008] The hydrophilic wiping layer is made of hydrophilic modified polyvinyl alcohol cotton layer, and the hydrophilic modified polyvinyl alcohol cotton layer is loaded with passivating cleaning components.
[0009] Further, by mass fraction, the raw materials for preparing the rust removal and polishing layer include: 30-55 parts of rubber, 15-25 parts of composite abrasive, 2-5 parts of the first corrosion inhibitor, 1-3 parts of crosslinking agent, 2-4 parts of foaming agent, and 30-50 parts of deionized water.
[0010] The composite abrasive is composed of nano-silicon carbide and microcrystalline corundum modified with silane coupling agent at a mass ratio of 1:(2-4). The nano-silicon carbide has a particle size of 30-80 nm, the microcrystalline corundum has a particle size of 5-15 μm, the porous foam matrix has a porosity of 70%-85%, a pore size of 20-100 μm, and a surface abrasive exposure rate of 30%-45%.
[0011] The range of aperture and abrasive exposure rate is a critical balance range that balances grinding and rust removal efficiency with low damage to the metal substrate. When the aperture is less than 20μm, the abrasive exposure is insufficient and the rust removal efficiency decreases. When the aperture is greater than 100μm, the grinding uniformity deteriorates and the surface roughness of the metal substrate doubles.
[0012] Further, by mass, the raw materials for preparing the functional adhesive layer include: 60-75 parts of modified waterborne polyurethane emulsion, 3-6 parts of silane coupling agent, 2-4 parts of phytic acid corrosion inhibitor, 0.5-1.5 parts of thickener, and 15-25 parts of deionized water.
[0013] The dry film thickness of the functional adhesive layer is 10-30 μm, and the interlayer peel strength between the rust removal and polishing layer and the hydrophilic wiping layer is not less than 12 N / cm.
[0014] The peel strength ensures that the product remains unspoiled and does not peel off after 100 cycles of repeated polishing and wiping. The peel strength is significantly higher than the interlayer bonding force of conventional adhesive cleaning wipes, which is 3-5 N / cm.
[0015] Furthermore, the hydrophilic modified polyvinyl alcohol cotton layer is a cross-linked modified open-cell polyvinyl alcohol foam, and the passivation and cleaning component is composed of benzotriazole derivatives and nonionic surfactants.
[0016] The porosity of the hydrophilic modified polyvinyl alcohol cotton layer is 88% to 95%, and the saturated water absorption rate is 8 to 12 times its own weight. The loading of the passivation cleaning component in the polyvinyl alcohol cotton layer is 1.5% to 3.5% of the dry weight of the polyvinyl alcohol cotton layer, and the thickness of the hydrophilic wiping layer is set to 2 to 8 mm.
[0017] Furthermore, the composite abrasive inside the rust removal and polishing layer is distributed in a gradient manner. Within a depth of 100μm extending from the outer surface of the rust removal and polishing layer inward, the abrasive mass ratio is 40% to 55% of the total abrasive. The abrasive mass ratio decreases layer by layer with increasing matrix depth. The composite abrasive is chemically bonded to the rubber matrix through a silane coupling agent. After 100 polishing cycles, the composite abrasive shedding rate is no higher than 3%.
[0018] The gradient distribution structure can release abrasive layer by layer while ensuring the sharpness of the surface grinding, thus extending the overall service life of the product.
[0019] Furthermore, the thickness ratio of the rust removal and polishing layer, the functional adhesive layer, and the hydrophilic wiping layer is (3-5):0.1:(2-4).
[0020] Furthermore, the present invention also provides a method for preparing a rust-removing cleaning wipe, which includes the following steps:
[0021] S1. Preparation of rust removal and polishing layer: Rubber and deionized water are mixed and heated to plasticize and disperse evenly. Composite abrasive and the first corrosion inhibitor are added and dispersed at high speed until the system is uniform. Then, crosslinking agent and foaming agent are added and stirred evenly. The mixture is injected into the mold and heated in stages to foam and cure. During the curing process, the composite abrasive settles naturally by its own weight, forming an abrasive gradient distribution structure with a dense outer layer and a sparse inner layer, thus producing a porous rust removal and polishing layer matrix.
[0022] S2. Interface activation and adhesive layer coating: The upper surface of the rust removal and grinding layer is subjected to low-temperature plasma activation treatment, and then the functional adhesive layer slurry is uniformly coated on the activated surface to form a wet adhesive layer.
[0023] S3, Three-layer composite co-curing: The pre-prepared hydrophilic modified polyvinyl alcohol cotton layer is bonded to the surface of the wet adhesive layer, and co-curing is carried out by gradient heating, so that the functional adhesive layer forms chemical bonds with the rust removal and polishing layer and the hydrophilic wiping layer respectively, to obtain a three-layer composite matrix;
[0024] S4. Passivation Function Loading and Post-treatment: The three-layer composite substrate is immersed in the passivation cleaning component solution. The passivation component is loaded into the hydrophilic wiping layer by vacuum negative pressure wetting. After removal, it is dried and cut into shape to obtain the finished rust removal cleaning wipe.
[0025] Furthermore, in step S1, the segmented heating foaming and curing process includes: first, pre-foaming at 50-60℃ for 10-20 minutes, then heating to 75-85℃ for constant temperature curing for 30-45 minutes, and finally controlling the overall heating rate to 1-2℃ / min to ensure that the composite abrasive settles slowly and forms a uniform gradient structure.
[0026] Furthermore, in step S2, the low-temperature plasma activation treatment uses air plasma, the coating thickness of the functional adhesive layer slurry is 50-100 μm, and the coating method is precision roller coating or blade coating.
[0027] Further, in step S3, the gradient temperature co-curing process includes: first, holding at 60-70℃ for 10-15 minutes to complete pre-gelling, then raising the temperature to 85-95℃ and holding for 20-30 minutes to complete main curing, and finally raising the temperature to 105-115℃ and holding for 10-15 minutes to complete curing.
[0028] Compared with existing technologies, the present invention provides a rust removal and cleaning wipe and its preparation method. The rust removal and grinding layer is in-situ doped with a first corrosion inhibitor component, which provides immediate corrosion inhibition to the fresh metal surface while grinding and removing rust. The functional adhesive layer is compounded with corrosion inhibitor factors, which serve as a corrosion inhibitor reservoir for continuous slow release and replenishment. The hydrophilic wiping layer is loaded with passivating cleaning components, which simultaneously form a passivating protective film on the metal surface during wiping and cleaning. The three layers work together to complete rust removal, process corrosion inhibition and surface passivation in a single operation, significantly improving the long-term anti-rust performance after rust removal.
[0029] The composite abrasive in the rust removal and grinding layer is distributed in a gradient with a denser outer layer and a sparser inner layer. The high abrasive content on the surface layer ensures the initial grinding sharpness and rust removal efficiency, while the internal abrasive is gradually released as the substrate wears down, maintaining long-term stable grinding performance. The silane-modified abrasive forms chemical bonds with the rubber matrix, which greatly reduces the abrasive shedding rate and significantly improves the product's service life.
[0030] The preparation process is highly controllable and suitable for large-scale production. It forms an abrasive gradient structure through the natural sedimentation effect of segmented heating and foaming, eliminating the need for additional gradient coating equipment. The process is simplified and the gradient uniformity is controllable. Vacuum negative pressure impregnation loads and passivates the components, and the loading amount is precisely controllable. The overall process flow is clear, the parameters are highly stable, and the batch consistency is good, making it suitable for large-scale industrial production. Attached Figure Description
[0031] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this invention. For those skilled in the art, other drawings can be obtained based on these drawings.
[0032] Figure 1 The preparation process flowchart is provided for an embodiment of the present invention. Detailed Implementation
[0033] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.
[0034] To address the challenge of achieving a multi-tiered protective effect encompassing immediate corrosion inhibition, continuous slow-release replenishment, and final surface passivation throughout the entire rust removal process, and the difficulty in simultaneously ensuring rust removal and polishing efficiency while maintaining long-term anti-rust performance after rust removal, please refer to... Figure 1 The following preferred technical solutions are provided.
[0035] All raw materials used in the embodiments of this invention are commercially available conventional industrial-grade raw materials. The hydrophilic wiping layer uses polyvinyl alcohol of type PVA1788; the rust removal and polishing layer uses styrene-butadiene rubber of type 1502; the silane coupling agent is KH-550; the nano silicon carbide has a particle size of 30-80 nm; the microcrystalline corundum has a particle size of 5-15 μm; the first corrosion inhibitor is triethanolamine; the crosslinking agent is 50 wt% glutaraldehyde aqueous solution; the foaming agent is azodicarbonamide; the modified waterborne polyurethane emulsion is anionic with a solid content of 30%; the phytic acid corrosion inhibitor is 50 wt% phytic acid aqueous solution; the thickener is hydroxyethyl cellulose; and the passivation and cleaning component is a compound of methylbenzotriazole and fatty alcohol polyoxyethylene ether AEO-9 in a mass ratio of 1:2.
[0036] Example 1
[0037] The purpose of this embodiment is to verify the feasibility of the present invention under low raw material ratios and mild process conditions.
[0038] (a) Structural components of a rust removal and cleaning wipe
[0039] The layers are arranged in a composite manner from top to bottom: a hydrophilic wiping layer, a functional adhesive layer, and a rust removal and polishing layer, with a thickness ratio of 3:0.1:2.
[0040] Rust removal and polishing layer raw materials (by mass parts): 30 parts rubber, 15 parts composite abrasive, 2 parts first corrosion inhibitor, 1 part crosslinking agent, 2 parts foaming agent, and 30 parts deionized water; the composite abrasive is a mixture of silane-modified nano-silicon carbide and microcrystalline corundum in a mass ratio of 1:2.
[0041] Functional adhesive layer raw materials (by mass parts): 60 parts modified waterborne polyurethane emulsion, 3 parts silane coupling agent, 2 parts phytic acid corrosion inhibitor, 0.5 parts thickener, and 15 parts deionized water.
[0042] Hydrophilic wiping layer: cross-linked modified open-cell polyvinyl alcohol foam with a porosity of 88% and a saturated water absorption rate of 8 times its own weight. The passivation cleaning component loading is 1.5% of the dry weight of the cotton layer.
[0043] (II) Preparation method
[0044] S1. Preparation of rust removal and polishing layer: Add rubber and deionized water to the reaction vessel, heat to 85℃ and stir to plasticize and disperse for 30 minutes until the system is uniform; add composite abrasive and the first corrosion inhibitor component, and disperse at high speed of 2500 r / min for 15 minutes; then add crosslinking agent and foaming agent and stir at low speed for 5 minutes to mix evenly; inject the mixture into the mold, heat to 50℃ at 1℃ / min for pre-foaming for 10 minutes, and then heat to 75℃ at 1℃ / min for constant temperature curing for 30 minutes; during the curing process, the composite abrasive settles naturally by its own weight, forming an abrasive gradient distribution structure with a dense outer layer and a sparse inner layer; cool and demold to obtain a porous rust removal and polishing layer matrix.
[0045] S2. Interface activation and adhesive layer coating: Air plasma is used to activate the upper surface of the rust removal and grinding layer. The treatment power is 150W and the treatment time is 20s. A functional adhesive layer slurry is applied to the activated surface using a precision roller, with a wet film thickness of 50μm, forming a wet adhesive layer.
[0046] S3. Three-layer composite co-curing: The pre-prepared hydrophilic modified polyvinyl alcohol cotton layer is attached to the surface of the wet adhesive layer and co-cured by gradient temperature increase according to the following procedure: 60℃ for 10min (pre-gel), 85℃ for 20min (main curing), and 105℃ for 10min (post-curing), so that the functional adhesive layer forms chemical bonds with the rust removal and polishing layer and the hydrophilic wiping layer respectively, to obtain a three-layer composite matrix.
[0047] S4. Passivation Function Loading and Post-treatment: The three-layer composite matrix is immersed in a 5wt% passivation cleaning component aqueous solution and wetted under negative pressure at a vacuum degree of -0.07MPa for 5 minutes; after being taken out and drained, it is dried at 60℃, cut into shape according to specifications, and the finished product is obtained.
[0048] (III) Performance Test Results
[0049] The test was conducted according to the test method described below, and the results are shown in Table 1. In this embodiment, the rust removal efficiency was 95.1%, the surface roughness Ra was 0.59 μm, the interlayer peel strength was 12.4 N / cm, the abrasive shedding rate after 100 cycles was 2.9%, the proportion of salt spray rust area after 72 hours was 8.3%, and the service life was 315 cycles.
[0050] Example 2 (Preferred Solution)
[0051] The purpose of this embodiment is to verify the synergistic effect of raw material ratio and process parameters within the preferred range.
[0052] (a) Structural components of a rust removal and cleaning wipe
[0053] The layers are arranged in a composite manner from top to bottom: a hydrophilic wiping layer, a functional adhesive layer, and a rust removal and polishing layer, with a thickness ratio of 4:0.1:3.
[0054] Rust removal and polishing layer raw materials (by mass parts): 43 parts rubber, 20 parts composite abrasive, 3.5 parts first corrosion inhibitor, 2 parts crosslinking agent, 3 parts foaming agent, and 40 parts deionized water; the composite abrasive is a mixture of silane-modified nano-silicon carbide and microcrystalline corundum in a mass ratio of 1:3.
[0055] Functional adhesive layer raw materials (by mass parts): 68 parts modified waterborne polyurethane emulsion, 4.5 parts silane coupling agent, 3 parts phytic acid corrosion inhibitor, 1 part thickener, and 20 parts deionized water.
[0056] Hydrophilic wiping layer: cross-linked modified open-cell polyvinyl alcohol foam with a porosity of 92%, a saturated water absorption rate of 10 times its own weight, and a passivation cleaning component loading of 2.5%.
[0057] (II) Preparation method
[0058] S1. Preparation of rust removal and polishing layer: Rubber and deionized water are added to the reaction vessel and heated to 90℃ for stirring and plasticizing dispersion for 40 min; composite abrasive and first corrosion inhibitor are added and dispersed at 3000 r / min for 20 min; then crosslinking agent and foaming agent are added and stirred evenly, and after being injected into the mold, the temperature is raised to 55℃ at 1.5℃ / min for pre-foaming for 15 min, and then the temperature is raised to 80℃ at 1.5℃ / min for constant temperature curing for 38 min; during the curing process, the abrasive naturally settles to form a gradient distribution, and after cooling and demolding, the rust removal and polishing layer substrate is obtained.
[0059] S2. Interface activation and adhesive layer coating: Air plasma is used to activate the surface of the rust removal and grinding layer at a power of 200W for 35s; a functional adhesive layer slurry is applied using a precision roller coating, with a wet film thickness of 75μm, forming a wet adhesive layer.
[0060] S3. Three-layer composite co-curing: The pre-made hydrophilic modified polyvinyl alcohol cotton layer is attached to the surface of the wet adhesive layer and co-cured according to the following procedure: 65℃ for 12min (pre-gel), 90℃ for 25min (main curing), and 110℃ for 12min (post-curing), so that the adhesive layer forms chemical bonds with the upper and lower layers to obtain a three-layer composite matrix.
[0061] S4. Passivation functional loading and post-treatment: The three-layer composite matrix is immersed in a 5wt% passivation cleaning component aqueous solution and wetted under negative pressure at a vacuum degree of -0.08MPa for 7min; after being taken out and drained, it is dried at 70℃ for 35min, cut into shape, and the finished product is obtained.
[0062] (III) Performance Test Results
[0063] The test results are shown in Table 1. In this embodiment, the rust removal efficiency is 97.8%, the surface roughness Ra is 0.51μm, the interlayer peel strength is 14.2N / cm, the abrasive shedding rate after 100 cycles is 2.0%, the proportion of salt spray rust area after 72 hours is 4.2%, and the service life is 392 cycles.
[0064] Example 3
[0065] The purpose of this embodiment is to verify the product performance under higher raw material ratios and stronger process conditions.
[0066] (a) Structural components of a rust removal and cleaning wipe
[0067] The layers are arranged in a composite manner from top to bottom: a hydrophilic wiping layer, a functional adhesive layer, and a rust removal and polishing layer, with a thickness ratio of 5:0.1:4.
[0068] Rust removal and polishing layer raw materials (by mass parts): 55 parts rubber, 25 parts composite abrasive, 5 parts first corrosion inhibitor, 3 parts crosslinking agent, 4 parts foaming agent, and 50 parts deionized water; the composite abrasive is a mixture of silane-modified nano-silicon carbide and microcrystalline corundum in a mass ratio of 1:4.
[0069] Functional adhesive layer raw materials (by mass parts): 75 parts modified waterborne polyurethane emulsion, 6 parts silane coupling agent, 4 parts phytic acid corrosion inhibitor, 1.5 parts thickener, and 25 parts deionized water.
[0070] Hydrophilic wiping layer: cross-linked modified open-cell polyvinyl alcohol foam with a porosity of 95%, a saturated water absorption rate of 12 times its own weight, and a passivation cleaning component loading of 3.5%.
[0071] (II) Preparation method
[0072] S1. Preparation of rust removal and polishing layer: Add rubber and deionized water to the reaction vessel, heat to 95℃ and stir to plasticize and disperse for 50 min; add composite abrasive and first corrosion inhibitor component, disperse at 4000 r / min for 25 min; then add crosslinking agent and foaming agent and stir to mix evenly, pour into mold and heat to 60℃ at 2℃ / min for pre-foaming for 20 min, then heat to 85℃ at 2℃ / min for constant temperature curing for 45 min; cool and demold to obtain rust removal and polishing layer substrate.
[0073] S2. Interface activation and adhesive layer coating: Air plasma is used to activate the surface of the rust removal and grinding layer, with a power of 250W and a time of 50s; a functional adhesive layer slurry is applied by precision roller coating, with a wet film thickness of 100μm, forming a wet adhesive layer.
[0074] S3. Three-layer composite co-curing: The pre-made hydrophilic modified polyvinyl alcohol cotton layer is attached to the surface of the wet adhesive layer and co-cured according to the following procedure: 70℃ for 15 min (pre-gel), 95℃ for 30 min (main curing), and 115℃ for 15 min (post-curing) to obtain a three-layer composite matrix.
[0075] S4. Passivation functional loading and post-treatment: The three-layer composite matrix is immersed in a 5wt% passivation cleaning component aqueous solution and wetted under negative pressure at a vacuum degree of -0.09MPa for 10min; after being taken out and drained, it is dried at 80℃ for 40min, cut into shape, and the finished product is obtained.
[0076] (III) Performance Test Results
[0077] The test results are shown in Table 1. In this embodiment, the rust removal efficiency is 96.5%, the surface roughness Ra is 0.54μm, the interlayer peel strength is 13.5N / cm, the abrasive shedding rate after 100 cycles is 2.2%, the proportion of salt spray rust area after 72 hours is 5.0%, and the service life is 358 cycles.
[0078] Comparative Example 1 (Commercially Available Standard Products)
[0079] Commercially available conventional three-layer rust removal and cleaning wipe: from top to bottom, it consists of a regular polyurethane sponge wiping layer, a water-based pressure-sensitive adhesive bonding layer, and a polyvinyl alcohol foam polishing layer; the polishing layer is physically mixed with brown corundum abrasive, without corrosion inhibitors, and the abrasive has no gradient distribution; the adhesive layer only serves an adhesive function and has no corrosion inhibitors; the wiping layer has no passivating components; it is prepared by manual application of adhesive and room temperature pressing, and the test results are shown in Table 1.
[0080] Comparative Example 2 (lacking corrosion inhibition and passivation functional layers)
[0081] The structure, raw materials and preparation method of Comparative Example 2 are basically the same as those of Example 2. The only difference is that the functional adhesive layer does not contain phytic acid corrosion inhibitors and the hydrophilic wiping layer does not contain passivation cleaning components. The test results are shown in Table 1.
[0082] Analysis of the interaction: The rust removal efficiency (94.3%) and abrasive shedding rate (2.1%) of Comparative Example 2 are close to those of Example 2 (97.8%, 2.0%), proving that its physical grinding performance is not significantly affected. However, its 72-hour salt spray rust return area ratio is as high as 26.8%, which is much higher than the 4.2% of Example 2. This shows that in the absence of the functional adhesive layer corrosion inhibitor and the hydrophilic wiping layer passivation component, even if the grinding layer still contains the first corrosion inhibitor, it cannot continuously inhibit secondary corrosion after grinding. This verifies that the three-level synergistic system of "physical grinding of rust removal grinding layer + chemical rust removal, corrosion inhibition transition of functional adhesive layer, and cleaning and passivation of hydrophilic wiping layer" described in this invention can achieve efficient rust removal and long-term rust prevention in a single wiping operation by setting different functional corrosion inhibitors in layers and releasing them in sequence.
[0083] Performance testing methods
[0084] The performance of the above embodiments and comparative samples was tested using the following methods:
[0085] Rust removal efficiency: After artificially accelerated rusting, the 45# carbon steel test piece was wiped 10 times with a pressure of 5N and a speed of 30 times / min. The percentage of rust layer removed was calculated using image analysis.
[0086] Surface roughness: The Ra value of the specimen after rust removal was tested using a roughness tester, and the average value of 3 different measurement points was taken.
[0087] Interlayer peel strength: In accordance with GB / T2792-2014 standard, a 180° peel test was conducted with a sample width of 25 mm and a tensile rate of 50 mm / min.
[0088] Abrasive shedding rate: After 100 reciprocating grinding cycles, the proportion of abrasive shedding mass to the initial total abrasive mass is calculated.
[0089] Rust prevention performance: The test was conducted for 72 hours according to the neutral salt spray test standard, and the percentage of rusted area of the test piece was observed.
[0090] Service life: The service life is the cumulative number of wipes when the rust removal efficiency drops to 80%.
[0091] The test results are shown in Table 1 below:
[0092] Rust removal efficiency (%) 95.1 97.8 96.5 81.7 94.3 Surface roughness Ra (μm) 0.59 0.51 0.54 0.89 0.53 Interlayer peel strength (N / cm) 12.4 14.2 13.5 3.6 13.9 Abrasive shedding rate after 100 cycles (%) 2.9 2.0 2.2 8.8 2.1 Percentage of area affected by salt spray corrosion after 72 hours (%) 8.3 4.2 5.0 63.1 26.8 Service life (times) 315 392 358 179 307
[0093] Results analysis:
[0094] (1) Rust removal efficiency and surface quality
[0095] The rust removal efficiency of all three embodiments is ≥95%, and the surface roughness Ra≤0.6μm, which is significantly better than the commercially available comparative example 1. This is due to the gradient distribution structure of the abrasive in the rust removal and grinding layer and the chemical anchoring effect of the silane coupling agent on the abrasive, which allows the abrasive to be fully exposed in the early stage of grinding and released layer by layer in the later stage, thus ensuring the initial sharpness and avoiding the substrate scratches caused by excessive abrasive shedding.
[0096] (2) Interlayer bonding strength and abrasive retention
[0097] The interlayer peel strength of the embodiments was ≥12N / cm and the abrasive shedding rate was ≤3%; the comparative example 1 had only 3.6N / cm and 8.8%. The difference is due to the fact that the functional adhesive layer of the present invention contains a silane coupling agent and introduces active groups on the surface of the rust removal and grinding layer through low-temperature plasma activation treatment, and then forms chemical bonds through gradient co-curing. In contrast, the comparative example 1 uses physical pressure-sensitive adhesive bonding, and the chemical bonding significantly improves the interlayer bonding strength, thereby reducing the abrasive shedding rate during use.
[0098] (3) Rust prevention performance (three-level collaborative system verification)
[0099] Comparative Example 2, which lacks only the phytic acid corrosion inhibitor in the functional adhesive layer and the passivation component in the hydrophilic wiping layer, shows a deterioration in its rust recurrence area ratio from 4.2% in Example 2 to 26.8%. Specifically, the first corrosion inhibitor component (triethanolamine) in the polishing layer is released during polishing, providing immediate chemical rust removal and initial protection; the phytic acid corrosion inhibitor in the adhesive layer continues to seep out after polishing, forming a corrosion-inhibiting transition layer; and the benzotriazole derivative in the wiping layer forms a film during the final wiping stage, providing long-lasting passivation protection. The absence of any one of these three components breaks the rust prevention chain. This comparative result directly verifies the technical contribution of the three-level synergistic system of this invention.
[0100] (4) Service life
[0101] Example 2 has a service life of 392 cycles, which is significantly better than Comparative Example 1's 179 cycles and also better than Comparative Example 2's 307 cycles. The main reason is that the abrasive gradient distribution and chemical bond anchoring together reduce the abrasive shedding rate, and the high peel strength of the functional adhesive layer prevents interlayer delamination, enabling the product to withstand more grinding cycles without failure.
[0102] in conclusion
[0103] The performance test results of the above embodiments and comparative examples confirm that the rust removal and cleaning wipe provided by the present invention, through a three-level synergistic system of "physical grinding of the rust removal and grinding layer + chemical rust removal, corrosion inhibition transition of the functional bonding layer, and cleaning and passivation of the hydrophilic wiping layer", as well as key technical features such as abrasive gradient distribution and chemical bonding between layers, simultaneously achieves efficient rust removal, low-damage grinding, long-term rust prevention and long service life in a single wiping operation. It solves the problems of simple stacked structure with single function and easy secondary rusting after rust removal in the prior art. Among them, Example 2 has the best comprehensive performance and is the preferred embodiment of the present invention.
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
[0105] The foregoing has only described certain exemplary embodiments of the present invention by way of illustration. Undoubtedly, those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the foregoing drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A rust-removing and cleaning wipe, characterized in that, It includes a hydrophilic wiping layer, a functional adhesive layer, and a rust removal and polishing layer, which are sequentially compounded from top to bottom; The rust removal and polishing layer is configured as a porous foam matrix, which is made of rubber through cross-linking foaming. The porous foam matrix is in situ doped with composite abrasive particles and a first corrosion inhibitor, and the composite abrasive particles are partially exposed on the inner wall and outer surface of the pores of the porous foam matrix. The functional adhesive layer is a modified water-based adhesive layer with compound corrosion inhibitors; The hydrophilic wiping layer is made of hydrophilic modified polyvinyl alcohol cotton layer, and the hydrophilic modified polyvinyl alcohol cotton layer is loaded with passivating cleaning components.
2. The rust-removing and cleaning wipe according to claim 1, characterized in that, The raw materials for preparing the rust removal and polishing layer, by weight, include: 30-55 parts of rubber, 15-25 parts of composite abrasive, 2-5 parts of the first corrosion inhibitor, 1-3 parts of crosslinking agent, 2-4 parts of foaming agent, and 30-50 parts of deionized water. The composite abrasive is made by mixing nano-silicon carbide with silane coupling agent surface modified with microcrystalline corundum in a mass ratio of 1:(2-4).
3. The rust-removing and cleaning wipe according to claim 1, characterized in that, The raw materials for preparing the functional adhesive layer, by weight, include: 60-75 parts of modified waterborne polyurethane emulsion, 3-6 parts of silane coupling agent, 2-4 parts of phytic acid corrosion inhibitor, 0.5-1.5 parts of thickener, and 15-25 parts of deionized water.
4. The rust-removing and cleaning wipe according to claim 1, characterized in that, The hydrophilic modified polyvinyl alcohol cotton layer is a cross-linked modified open-cell polyvinyl alcohol foam, and the passivation and cleaning component is composed of benzotriazole derivatives and nonionic surfactants.
5. The rust-removing and cleaning wipe according to claim 2, characterized in that, The composite abrasive inside the rust removal and polishing layer is distributed in a gradient state, and the mass ratio of the abrasive decreases layer by layer with the increase of the matrix depth. The composite abrasive is chemically bonded to the rubber matrix through a silane coupling agent.
6. The rust-removing and cleaning wipe according to claim 1, characterized in that, The thickness ratio of the rust removal and polishing layer, the functional adhesive layer, and the hydrophilic wiping layer is (3-5):0.1:(2-4).
7. A method for preparing a rust-removing cleaning wipe, used to prepare a rust-removing cleaning wipe as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Preparation of rust removal and polishing layer: Rubber and deionized water are mixed and heated to plasticize and disperse evenly. Composite abrasive and the first corrosion inhibitor are added and dispersed at high speed until the system is uniform. Then, crosslinking agent and foaming agent are added and stirred evenly. The mixture is injected into the mold and heated in stages to foam and cure. During the curing process, the composite abrasive settles naturally by its own weight, forming an abrasive gradient distribution structure with a dense outer layer and a sparse inner layer, thus producing a porous rust removal and polishing layer matrix. S2. Interface activation and adhesive layer coating: The upper surface of the rust removal and grinding layer is subjected to low-temperature plasma activation treatment, and then the functional adhesive layer slurry is uniformly coated on the activated surface to form a wet adhesive layer. S3, Three-layer composite co-curing: The pre-prepared hydrophilic modified polyvinyl alcohol cotton sheet is bonded to the surface of the wet adhesive layer, and co-curing is carried out by gradient heating, so that the functional adhesive layer forms chemical bonds with the rust removal and polishing layer and the hydrophilic wiping layer respectively, to obtain a three-layer composite matrix; S4. Passivation Function Loading and Post-treatment: The three-layer composite substrate is immersed in the passivation cleaning component solution. The passivation component is loaded into the hydrophilic wiping layer by vacuum negative pressure wetting. After removal, it is dried and cut into shape to obtain the finished rust removal cleaning wipe.
8. The method for preparing the rust-removing cleaning wipe according to claim 7, characterized in that, In step S1, the segmented heating foaming and curing process includes: first, pre-foaming at 50-60℃ for 10-20 minutes, then heating to 75-85℃ for constant temperature curing for 30-45 minutes, and finally controlling the overall heating rate to 1-2℃ / min.
9. The method for preparing the rust-removing and cleaning wipe according to claim 7, characterized in that, In step S2, air plasma is selected for the low-temperature plasma activation treatment.
10. The method for preparing the rust-removing cleaning wipe according to claim 7, characterized in that, In step S3, the gradient temperature co-curing process includes: first, pre-gelling is completed by holding at 60-70℃ for 10-15 minutes, then the temperature is increased to 85-95℃ and held for 20-30 minutes to complete the main curing, and finally the temperature is increased to 105-115℃ and held for 10-15 minutes to complete the curing.